Análise de metais pesados no Sistema Aquífero Bauru em Mato Grosso do Sul - Uechi, Denise Aguena; Gabas, Sandra Garcia; Lastoria, Giancarlo [UNESP] (FapUNIFESP (SciELO), 2017)
Heavy metals are contaminants of great concern in the aquifers due to their toxicity at certain concentration and difficult remediation. This study aimed to analyze the concentrations of Cu, Cr, Fe, Mn and Zn present in Bauru Aquifer System in Mato Grosso do Sul State, from 2009 to 2013. The content of Cu, Cr and Zn were within the limits of drinking water from Brazilian legislation, unlike Mn and Fe. The use of vinasse in fertigation of sugar cane cultivation and mineral tanning leather can influence the quality of groundwater in the outcropping area of the aquifer. This study reinforces the importance of monitoring groundwater quality in order to establish a zoning of vulnerability to pollution through control measures, prevention and remediation.
Analysis of heavy metals in the Bauru Aquifer System in Mato Grosso do Sul
Keywords: Contamination; Drinking water; Free aquifer; Heavy metals